Polarization switching and injection locking in vertical-cavity surface-emitting lasers subject to parallel optical injection - Quirce, Ana; Pérez, Pablo; Popp, Alexandra; Valle, Ángel; Pesquera, Luis; Hong, Yanhua; Thienpont, Hugo; Panajotov, Krassimir (Optics letters, 2016)
Polarization switching in a long-wavelength vertical-cavity surface-emitting laser (VCSEL) under parallel optical injection is analyzed in a theoretical and experimental way. For the first time, to our knowledge, we report experimentally a state in which injection locking of the parallel polarization and excitation of the free-running orthogonal polarization of the VCSEL are simultaneously obtained. We obtain very simple analytical expressions that describe both linear polarizations. We show that the power of both linear polarizations depend linearly on the injected power in such a way that the total power emitted by the VCSEL is constant. We perform a linear stability analysis of this solution to characterize the region of parameters in which it can be observed. Our measurements qualitatively confirm the previous theoretical predictions.